Acute systemic knockdown of Atg7 is lethal and causes pancreatic destruction in shRNA transgenic mice. Issue 12 (2nd December 2022) - Mainz, Laura; Sarhan, Mohamed A. F. E.; Roth, Sabine; Sauer, Ursula; Kalogirou, Charis; Eckstein, Markus; Gerhard-Hartmann, Elena; Seibert, Helen-Desiree; Voelker, Hans-Ulrich; Geppert, Carol; Rosenwald, Andreas; Eilers, Martin; et al.
ABSTRACT: The notion that macroautophagy/autophagy is a potentially attractive therapeutic target for a variety of diseases, including cancer, largely stems from pre-clinical mouse studies. Most of these examine the effects of irreversible and organ confined autophagy deletion using site specific Cre -loxP recombination of the essential autophagy regulating genes Atg7 or Atg5 . Model systems with the ability to impair autophagy systemically and reversibly at all disease stages would allow a more realistic approach to evaluate the consequences of authophagy inhibition as a therapeutic concept and its potential side effects. Here, we present shRNA transgenic mice that via doxycycline (DOX) regulable expression of a highly efficient miR30-E-based shRNA enabled knockdown of Atg7 simultaneously in the majority of organs, with the brain and spleen being noteable exceptions. Induced animals deteriorated rapidly and experienced profound destruction of the exocrine pancreas, severe hypoglycemia and depletion of hepatic glycogen storages. Cessation of DOX application restored apparent health, glucose homeostasis and pancreatic integrity. In a similar Atg5 knockdown model we neither observed loss of pancreatic integrity nor diminished survival after DOX treatment, but identified histological changes consistent with steatohepatitis and hepatic fibrosis in the recovery period after termination of DOX. Regulable Atg7 -shRNA mice are valuable tools that will enable further studies on the role of autophagy impairment at various disease stages and thereby help to evaluate the consequences of acute autophagy inhibition as a therapeutic concept. Abbreviations: ACTB: actin, beta; AMY: amylase complex; ATG4B: autophagy related 4B, cysteine peptidase; ATG5: autophagy related 5; ATG7: autophagy related 7; Cag: CMV early enhancer/chicken ACTB promoter; Col1a1 : collagen, type I, alpha 1; Cre: cre recombinase; DOX: doxycycline; GCG: glucagon; GFP: green fluorescent protein; INS: insulin; LC3: microtubule-associated protein 1 light chain 3; miR30-E: optimized microRNA backbone; NAFLD: non-alcoholic fatty liver disease; NASH: non-alcoholic steatohepatitis; PNLIP: pancreatic lipase; rtTA: reverse tetracycline transactivator protein; SQSTM1/p62: sequestome 1; TRE: tetracycline responsive element.